The Influence of Environment, Social and Governance (ESG) on Financial Performance: The Role of Ownership Structure as a Moderating Variable - Christina Sososutiksno; Jabida Latuamury; Kathleen Asyera Risakotta; Shella Gilby Sapulette; Rita J.D. Atawarman (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The purpose of this study is to examine the influence of ESG on corporate financial performance, moderated by ownership structure, in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2023 period. This study used secondary data in the form of annual reports and corporate sustainability reports. The study sampled 65 companies, and the analysis technique used was moderated regression analysis (MRA). The data analysis results indicate that ESG has no effect on corporate financial performance, and institutional ownership strengthens the influence of ESG on financial performance.